Lenny Krayzelberg at 180 m of his World-record 200 m Race at the 1999 Pan Pacific Championships in Sydney - Rushall, B. S.
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Lenny Krayzelberg at 180 m of his World-record 200 m race . While Lenny Krayzelberg is the new world-record holder in backstroke events, his stroke could still be improved. The position of entry of both arms could be improved so that delays caused by repositioning do not occur before effective propulsion begins. Entries similar to those of Martin Lopez-Zubero, exhibited in another analysis in this journal, would be better. Matching the right arm pull with the stroking pattern of the left arm would improve the technique and result in performance enhancement. The streamlining and head position demonstrated by Lenny Krayzelberg is worthy of emulation by all backstrokers.